Multivariate and hash-based post-quantum digital signatures. - Pereira, Geovandro Carlos Crepaldi Firmino (2015)
The conventional digital signature schemes widely used today may have their security threatened with the possibility of the rising of a large quantum computer. Moreover, such schemes are not entirely suitable for utilization on very constrained-resource platforms. Therefore, there is a need to look at alternatives that present reasonable security in the medium and long term, in addition to attaining acceptable performance when few resources are available. This work provides more efficient multivariate and hash-based post-quantum digital signatures and targets the deployment in scenarios like Internet of Things and Wireless Sensor Networks where the typical devices are very resource-constrained. In the context of multivariable quadratic digital signatures we describe a new technique that attempts to minimize the main drawbacks of these schemes, the large key sizes. The new technique explores certain structures compact matrix rings. Some of the analyzed matrix rings are not secure (one of the attacks runs in polynomial time). Other less compact matrix rings are investigated and they apparently do not suffer a polynomial time attack, but unfortunately are still far from deployment on very constrained platforms. On the other hand, this work describes a method for hash-based signatures providing a 2/3 reduction of the signature sizes in the Merkle-Winternitz multi-time signature scheme. In fact, the signature sizes constitute the main bottleneck of these schemes. The improvement also leads to a 2/3 reduction in the run times (key generation, signing and verifying) and in energy consumption for all these operations on an AVR ATmega128L microcontroller, typically found in Wireless Sensor Networks. This result is much more promising for the deployment in an IoT scenario.